Genome assembly of primitive cultivated potato Solanum stenotomum provides insights into potato evolution. Issue 10 (29th July 2021) - Yan, Lang; Zhang, Yizheng; Cai, Guangze; Qing, Yuan; Song, Jiling; Wang, Haiyan; Tan, Xuemei; Liu, Chunsheng; Yang, Mengping; Fang, Zhirong; Lai, Xianjun
Abstract: Genetic diversity is the raw material for germplasm enhancement. Landraces and wild species relatives of potato, which contain a rich gene pool of valuable agronomic traits, can provide insights into the genetic diversity behind the adaptability of the common potato. The diploid plant, Solanum stenotomum (Sst), is believed to have an ancestral relationship with modern potato cultivars and be a potential source of resistance against disease. Sequencing of the Sst genome generated an assembly of 852.85 Mb (N50 scaffold size, 3.7 Mb). Pseudomolecule construction anchored 788.75 Mb of the assembly onto 12 pseudochromosomes, with an anchor rate of 92.4%. Genome annotation yielded 41, 914 high-confidence protein-coding gene models and comparative analyses with closely related Solanaceae species identified 358 Sst-specific gene families, 885 gene families with expansion along the Sst lineage, and 149 genes experiencing accelerated rates of protein sequence evolution in Sst, the functions of which were mainly associated with defense responses, particularly against bacterial and fungal infection. Insights into the Sst genome and the genomic variation of cultivated potato taxa are valuable in elaborating the impact of potato evolution in early landrace diploid and facilitate modern potato breeding.